Tools of Visual Merchandising in Slovenian Grocery Stores in Practice (Challenges of the Future, 2025)
Research Question (RQ): Distribution of products in stores should contribute to better selling. In the article we want to test if such methods are used in the case of selected Slovenian grocery stores.Purpose: The article tries to demonstrate on two case studies presence of merchandising in Slovenian grocery stores.Method: Based on literature review experiment with observation is carried out in two grocery stores.Results: Merchandising methods are psychological trick that count on individuals’ impulsiveness to increase the selling. Testing them on selected cases in Slovenia shows existence of such “tricks” also in Slovenian grocery stores, despite merchandising tactics are not consistently applied.Organization: The research results can contribute to organisational awareness of potential sloppiness in execution of merchandising.Society: The article potentially raise awareness of selling strategies implemented by stores and consequently should lead to more conscious buying.Originality: Article contributes to observational study in the field and can serve as a pilot study for further development of methodology for more systemic approach.Limitations / further research: Empirical research was conducted only on two cases which makes results demonstrative but not conclusive, The approach should be implemented on bigger sample.
Keywords: merchandising; store layout; arrangement of goods; purchase management; impulse purchase